Driving Cells with Light‐Controlled Topographies. Issue 14 (20th May 2019) - Puliafito, Alberto; Ricciardi, Serena; Pirani, Federica; Čermochová, Viktorie; Boarino, Luca; De Leo, Natascia; Primo, Luca; Descrovi, Emiliano
Abstract: Cell–substrate interactions can modulate cellular behaviors in a variety of biological contexts, including development and disease. Light‐responsive materials have been recently proposed to engineer active substrates with programmable topographies directing cell adhesion, migration, and differentiation. However, current approaches are affected by either fabrication complexity, limitations in the extent of mechanical stimuli, lack of full spatio‐temporal control, or ease of use. Here, a platform exploiting light to plastically deform micropatterned polymeric substrates is presented. Topographic changes with remarkable relief depths in the micron range are induced in parallel, by illuminating the sample at once, without using raster scanners. In few tens of seconds, complex topographies are instructed on demand, with arbitrary spatial distributions over a wide range of spatial and temporal scales. Proof‐of‐concept data on breast cancer cells and normal kidney epithelial cells are presented. Both cell types adhere and proliferate on substrates without appreciable cell damage upon light‐induced substrate deformations. User‐provided mechanical stimulation aligns and guides cancer cells along the local deformation direction and constrains epithelial colony growth by biasing cell division orientation. This approach is easy to implement on general‐purpose optical microscopy systems and suitable for use in cell biology in a wide variety of applications. Abstract : A platform is presented, allowing light‐controlled morphological deformations of micro‐structured substrates for cell cultures. Morphology modifications are induced with high resolution by illuminating the substrate with arbitrary light patterns that can be dynamically provided at any time during cell growth. This technique is implemented on a conventional microscope for fluorescence bio‐imaging, thus allowing direct observations while light‐triggering mechanical cues.